2019
DOI: 10.1002/epi4.12325
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and etiological characteristics of epilepsy in people from Niger: a hospital‐based study from a tertiary care referral center of Niamey, Niger

Abstract: Objectives Epilepsy constitutes a major public health concern in the world particularly in developing countries, especially in sub‐Saharan African countries. We designed this study to evaluate epilepsy management at a tertiary referral center in Niger to obtain a comprehensive understanding to determine the intrahospital deficiencies to improve and to make recommendations in terms to improve epilepsy management in Niger. Methods We conducted a retrospective study at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 19 publications
5
24
0
Order By: Relevance
“…A Nigerian study also reported the prescription of only the first‐generation AEDs (Igwe et al., 2014). As in the study carried out at the National Hospital of Niamey (Assadeck et al., 2019), VPA was the most AED used in the present study. In Mali, a study reported phenytoin as the most AED used (Nimaga et al., 2002).…”
Section: Discussionsupporting
confidence: 60%
“…A Nigerian study also reported the prescription of only the first‐generation AEDs (Igwe et al., 2014). As in the study carried out at the National Hospital of Niamey (Assadeck et al., 2019), VPA was the most AED used in the present study. In Mali, a study reported phenytoin as the most AED used (Nimaga et al., 2002).…”
Section: Discussionsupporting
confidence: 60%
“…In this study, we evaluate knowledge, attitudes, and practices about epilepsy among primary and secondary school teachers in the city of Niamey, capital of Niger. Because epilepsy mainly affects people younger than 20 years in Niger (Assadeck et al, ), we have chosen to specifically conduct the survey among primary and secondary school teachers who are responsible for the social and educational development of people in this age group and to transmit them targeted awareness messages about epilepsy so that they can transmit these messages to a larger number of students to avoid the rejection of epileptic students by their peers. The majority of teachers (62.1%) who completed the questionnaire had a bachelor degree in education signifying a high level of education.…”
Section: Discussionmentioning
confidence: 99%
“…In Niger, epilepsy is poorly studied, and there is no study realized in the general population determining the incidence and prevalence of this condition. However, a recent study reports a hospital frequency of epilepsy of 29.5%, affecting mainly men and people younger than 20 years (Assadeck et al, ). In sub‐Saharan Africa, epilepsy remains a major public health concern with significant economic and socio‐cultural consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Seizure disorders comprised 6.4% of NDs in the series and were significantly associated with HIV infection, OR 15.7. A high burden of seizure disorders with frequencies ranging from 6–12.6% is reported in similar hospital based studies in adults in SSA 3 , 5 , 52 . The added burden of seizures in HIV in SSA is reflected by their reported high frequency in HIV infection, occurring in up to 10% of patients presenting with advanced immunosuppression, with OIs as their main cause 5 , 15 , 53 , 54 .…”
Section: Discussionmentioning
confidence: 65%